Peningkatan Kepatuhan Hand Hygiene pada Tenaga Kesehatan dan Keluarga Pasien sebagai Upaya Pencegahan Infeksi Nosokomial - Martins, Noelio Auxilio Pedro; Nurwijayanti, Nurwijayanti (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Nosocomial infections remain a major patient safety issue, particularly in Emergency Departments (ED) with high patient flow. Hand hygiene is the most effective preventive measure; however, compliance among healthcare workers and patient families at the Emergency Department of Hospital Nacional Guido Valadares (HNGV) remains low due to limited facilities, inadequate education, and high workload. Objective: To improve hand hygiene compliance among healthcare workers and patient families through a multimodal intervention as part of nosocomial infection prevention efforts in the ED of HNGV. Method: This residency program with anylisis fishbone, SWOT, USG are implemented assessment, intervention, and evaluation stages. Compliance was measured using direct observation based on the WHO Five Moments before and after intervention. Interventions included structured education, improved hand hygiene facilities, visual reminders, and audit-feedback mechanisms. Results: Pre-intervention compliance was 48% among healthcare workers and 42% among patient families, with an overall rate of 45%. Post-intervention results showed significant improvement: healthcare worker compliance increased to 82%, family compliance to 76%, and overall compliance reached 79%. The greatest improvement occurred in the moments before patient contact and after touching patient surroundings. Conclusion: The multimodal intervention effectively enhanced hand hygiene compliance in the ED of HNGV. Sustained improvement requires ongoing education, adequate facilities, and regular monitoring to support a strong patient safety culture and reduce nosocomial infection risks.